2021
DOI: 10.2147/ccide.s324396
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Dentists and Students to Detect Caries by Using the International Caries Detection and Assessment System

Abstract: To evaluate the ability of dentists and dental students to detect caries by using the International Caries Detection and Assessment System (ICDAS). Materials and Methods: A cross-sectional study was conducted in Riyadh city and in the College of Dentistry at King Saud University (KSU) in Saudi Arabia. The study sample included a cluster sampling of 50 private clinics (100 dentists) and all 3rd-, 4th-, and 5th-year students (393 students). Data were collected using an electronic questionnaire. The ability score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…(2021) reported that dentists in KSA were unable to adequately detect caries using the ICDAS criteria. 13 This indicates the necessity of appropriate clinical training during dental undergraduate programs, as well as continuous education after graduation; such training improves the early diagnosis of dental caries when applying the ICDAS II criteria. G.V.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) reported that dentists in KSA were unable to adequately detect caries using the ICDAS criteria. 13 This indicates the necessity of appropriate clinical training during dental undergraduate programs, as well as continuous education after graduation; such training improves the early diagnosis of dental caries when applying the ICDAS II criteria. G.V.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the majority of the respondents were junior dentists with less than three years of private practice experience, several acknowledged not utilizing ICDAS since they did not obtain explicit guidance during their undergraduate studies [11]. In tandem, Al Dhubayb et al [20] discovered that only 23% of the 100 private dentists surveyed used the ICDAS code in their practice, citing a lack of training as a contributing issue. Although ICDAS was established in the early to mid-2000s, several Malaysian dental schools just started using it to replace the DMF index in the curriculum less than 10 years ago [8].…”
Section: Discussionmentioning
confidence: 99%
“…Este sistema clasifica la caries de 0 a 6, donde 0 es anatomía normal, 1 es mancha blanca o café en seco, 2 es mancha blanca o café en húmedo, 3 es esmalte fracturado o microcavidad y así sucesivamente hasta llegar al 6, que equivale a cavidad extensa. Dicha clasificación fue establecida para detectar lesiones tempranamente, aun sin que haya una cavidad en el diente(29). Algunos odontogramas incluyen el icdas, pero esto no sucede con el nuestro, aun cuando varios docentes han insistido en sus bondades.…”
unclassified